Present Strategy for REBOA Management After Catheter Placement: A Current Suggestion From the Japanese Society of DIRECT - Kurihara, Yutaro; Tamura, Satoshi; Maruhashi, Takaaki; Matsumura, Yosuke (Journal of Endovascular Resuscitation and Trauma Management, 2022)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been accepted as a useful bridging tool to definitive hemostasis in refractory hemorrhagic shock. Although there is insufficient evidence of the target blood pressure under the utilization of REBOA, it may be reasonable to avoid excessive blood pressure elevation. Invasive blood pressure monitoring proximal to the aortic occlusion is desirable during REBOA. The zone of the aorta is selected and changed according to the location of injuries and the physiological conditions. The key to successful REBOA management is to set up an independent REBOA coordinator for systemic management. This review article aims to explain the procedures of proper REBOA management, so as to fill the knowledge gap between educational courses, which highlight the indications and safe procedures of the device, and the critical settings faced in clinical practice.